Risk factors of post‐tonsillectomy hemorrhage in adults. Issue 6 (14th November 2020) - Inuzuka, Yoshiaki; Mizutari, Kunio; Kamide, Daisuke; Sato, Michiya; Shiotani, Akihiro
Abstract: Objective: Tonsillectomy is an essential surgery and is conducted on both children and adults. However, the risk factors of post‐tonsillectomy hemorrhage for adult patients remain unclear. In this study, we analyzed post‐tonsillectomy hemorrhage in adult patients. Methods: We retrospectively analyzed 325 adult patients who underwent a tonsillectomy between 2014 and 2018 in our facilities. Results: The average age of this study's population was 31.7 ± 10.5 years (range: 19‐70 years), and 250 (76.9%) patients were male. Overall, post‐tonsillectomy hemorrhage occurred in 71 (21.8%) patients and 5 (1.5%) patients required a second surgery for hemostasis. Post‐tonsillectomy hemorrhage often occurred on postoperative day zero or six. Using multiple logistic regression analysis, current smoking status (odds ratio 3.491; 95% confidence interval 1.813‐6.723), male sex (odds ratio 3.924; 95% confidence interval 1.548‐9.944), and perioperative non‐steroidal anti‐inflammatory drug administration (odds ratio 7.930; 95% confidence interval 1.004‐62.64) were revealed as overall post‐tonsillectomy hemorrhage risk factors. To analyze the hemorrhage period after tonsillectomy, we categorized the post‐tonsillectomy hemorrhage patients into the primary (bleeding within postoperative day one) and secondary hemorrhage (bleeding on or after postoperative day two) groups. The current smoking status and older age were risk factors for primary hemorrhage and the current smoking status and sex (male) were risk factors for secondary hemorrhage. Conclusions: In this study, smoking status, sex, and perioperative non‐steroidal anti‐inflammatory drug administration were the clinical risk factors for adult post‐tonsillectomy hemorrhage. Thus, smoking cessation is, at least, mandatory for patients who receive tonsillectomy to avoid post‐tonsillectomy hemorrhage. Level of Evidence: 4 Abstract : Periods and categories of PTH. Among the 71 patients, eight had primary hemorrhage, and 63 had secondary hemorrhage. There were two peaks of frequency on postoperative days 0 and 6.